Conceptual Modell of Efficient Market of Databases in Iran - Mahshid Eltemasi (Iranian Journal of Information Processing & Management, 2017)
Purpose: The main purpose of this article is conceptual modeling of market efficiency of information databases, there are 3 main questions in this article: 1) what are the components of the efficient market? 2) Is the database markets an efficient market? 3)  How is the mental model of the efficient market databases? Methodology:  In order to achieve that, summarizing content analysis techniques was used by reviewing literatures during the two-step analysis, and coding processes extracted the main components of efficient markets, then provided a check list from component and sent to business unit managers of 9 major databases. Finding: We found that fourth categories for information database efficient markets: Linearity is most important and then to order, are logic and rationality, and Information-centric, trading volume reached fourth place, so we can say the information database markets are efficient, and findings of check list showed that the market for databases can be regarded as efficient markets. Results: and therefore we traced the conceptual model of efficient markets in Information Databases.